A Method for Allocating Funds to Investment Projects when Returns are Subject to Uncertainty - Cord, Joel (Management Science, 1964)
A method is developed for optimally selecting capital investments with uncertain returns, under conditions of limited funds and a constraint on the maximum average variance allowed in the final investment package. The concepts involved in the analysis are somewhat related to Markowitz's work on the portfolio problem. Dynamic programming is used to compute solutions.